2019
DOI: 10.1119/1.5088467
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Newton’s Second Law

Abstract: Physics instructors recognize the value of kinesthetic experience in learning fundamental physics concepts. We describe a kinesthetic experiment appropriate for both college and high school physics students. The experiment helps students achieve an intuitive understanding of Newton’s second law in a way they find quite enjoyable. It was devised by one of us over 20 years ago and has been performed by thousands of students at Loyola Marymount University (LMU) and by students at some Los Angeles area high school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…[24,[64][65][66][67][68][69]). Perhaps unsurprisingly, KLAs are relatively common in the physics literature as a way of leveraging students' bodily experience to make sense of physics phenomena [70,71]. KLAs have been shown as potentially effective means for engaging students [72] and improving learning outcomes in particular settings [62].…”
Section: The Body and Learning Physics: Existing Per Work And Our mentioning
confidence: 99%
“…[24,[64][65][66][67][68][69]). Perhaps unsurprisingly, KLAs are relatively common in the physics literature as a way of leveraging students' bodily experience to make sense of physics phenomena [70,71]. KLAs have been shown as potentially effective means for engaging students [72] and improving learning outcomes in particular settings [62].…”
Section: The Body and Learning Physics: Existing Per Work And Our mentioning
confidence: 99%
“…Previous physics education research attempts on embodied learning to introduce basic concepts and phenomena have included kindergarten students (Herakleioti & Pantidos, 2016;Hadzigeorgiou et al, 2008), secondary students for challenging concepts (DeStefano et al, 2020;Coletta et al, 2019) or university students to re-explore some previously taught concepts (Whitworth et al, 2014;Scherr et al, 2012), providing a positive impact when going beyond just the design proposal of the activities. Concepts in mechanics have a direct link with the human body and are an important presence in the daily life of students from a young age.…”
Section: Discussionmentioning
confidence: 99%
“…A prime example is the research of Levin et al (1990) dealing with 6 th -grade students' alternative ideas regarding linear velocity during circular motion, which showed, among other things, that kinesthetic intervention that countered a specific misconception led to a significant improvement in their understanding. As part of a broader curriculum for teaching physics, called Thinking in Physics (TIP), designed to develop a strong understanding of key physics concepts by middle and high school students, kinesthetic experiences were designed and implemented for Newton's second law (Coletta et al, 2019) but their effect on students' overall progress is unknown. As research has shown that preschool children are ready to learn various scientific ideas, Hadzigeorgiou et al (2008) compared the performance of two groups of preschool children who had participated in two alternative interventions for mechanical balance.…”
Section: Literature Reviewmentioning
confidence: 99%